Metabolic Pathway Engineering (Methods in Molecular Biology, 2020)
This book illustrates experimental and computational methodologies used to achieve cost effective biological processes for the production of fuels and biochemicals through multiple approaches to increasing yield, titers, and productivity in a robust host. The volume includes the most recent and cutting-edge aspects of pathway engineering, flux analysis, and metabolic enzyme engineering. Each chapter highlights the complexity and challenges of the problem as well as the methods used to solve this problem or changes needed in current methods. As a part of the highly successful Methods in Molecular Biology series, chapters include the kind of detailed implementation advice that gives researchers a much needed boost. Authoritative and practical, Metabolic Pathway Engineering benefits not only scientists working on more fundamental aspects of this endeavor but also those in the biochemical industry working on strain engineering for robust industrial processes